Evaluating cognitive competences in interaction - Rasmussen, Gitte; Brouwer, C. E.; Day, Dennis (Pragmatics & beyond., 2012)
This paper presents a study of how teenage boys with learning disabilities evaluate co-participants' 'cognitive' or 'mental' state competences in interaction ("you are sick in the head"). The evaluations emerge out of disputes and disagreements about social experiences and end these disputes by excluding the co-participant from further talk on current topics. The study shows thus how 'mental' state evaluations become insults: In and through the use of 'mental' state evaluations in actions in which the boys triumph over, or 'win' the dispute as they exclude others from participation in on-going